Keterkaitan Islam Dan Komunikasi Interpersonal - Fadhlan (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2019)
This study is important to understand the interrelationship of Islamic communication with interpersonal communication. The basic concept needs to be understood that humans are spiritual and physical beings, so what is inside us cannot be fully understood by others, if we do not want to reveal to them. Other people cannot understand our ideas, feelings, intentions and intentions if we do not consciously convey to them. Interpersonal communication is communication that occurs in two directions reciprocally between two or more people. Interpersonal communication is very appropriate to do, because between communicators and communicants can discuss each other about various problems. Communicators can see directly the communicant response during the communication process. Interpersonal communication is practiced by many communicators as a process of approach to communicants, such as completing a problem, da'wah, trial process and others. As one effective method of communication, interpersonal communication still exists even though there are many methods of communication that are currently developing, such as virtual communication that communicators and communicants do not have to meet to communicate. Basically, interpersonal communication indirectly creates mutual respect between communicators and communicants. So that this method is very effective for the process of problem solving between communicants and communicators.